Die Nederlandse Geloofsbelydenis / Confessio Belgica en die Bybel in 1561 - Bosman, Hendrik L (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
As part of the celebration of the Confessio Belgica (450 years after it was written) this contribution focuses on the hermeneutical frame presupposed by and interpretation of the Bible in the confession. It is clear that Guido de Bres (main author of the confession) was well read and was able to formulate the confession in such a way that it resonated with the protestant communities of faith in the southern Netherlands – what initially was intended as a polemical attempt to distantiate themselves from the Anabaptists soon became accepted a confession of faith. The Confessio Belgica does not quote directly from Scripture but refers to biblical verses and phrases by means of free association. The use of Scripture in the Confessio Belgica is pre-critical because the literal sense of the Bible is paramount and it does not reflect self critically in terms of its own presuppositions – this does not imply that the confession is intellectually suspect or deficient! The question is also posed whether the Confessio Belgica can continue to be understood as a “repetition of Sacred Scripture” or must it be held accountable for the way in which it interpreted Scripture in the sixteenth century to maintain relevance in the twenty-first century?